1993
DOI: 10.1212/wnl.43.5.919
|View full text |Cite
|
Sign up to set email alerts
|

MRI changes in intracranial hypotension

Abstract: We report seven patients with the syndrome of intracranial hypotension who were referred to Memorial Sloan-Kettering, primarily because of suspicion of meningeal tumor or infection raised by the finding of meningeal enhancement on MRI. In three patients, symptoms occurred after lumbar puncture; in four, there was no clear precipitating event. Lumbar puncture after MRI in six patients revealed low CSF pressure (six patients) and pleocytosis or high protein, or both (four patients). Three patients had subdural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
211
1
6

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(229 citation statements)
references
References 0 publications
9
211
1
6
Order By: Relevance
“…These symptoms worsen within fifteen minutes after sitting or standing. Meningeal enhancement is frequently observed [2]. We present a case of CSF hypovolemia with dissociation between its severity and the MRI findings.…”
Section: Sirmentioning
confidence: 84%
“…These symptoms worsen within fifteen minutes after sitting or standing. Meningeal enhancement is frequently observed [2]. We present a case of CSF hypovolemia with dissociation between its severity and the MRI findings.…”
Section: Sirmentioning
confidence: 84%
“…2,3 CNP after dural puncture is attributed to continuous CSF leakage through the dural hole. 4 Magnetic resonance imaging has demonstrated that this results in intracranial hypotension with descent of the brain, even in the supine position, causing traction of the sixth nerve and pain-sensitive structures. 4 The stretching of the nerve is thought to cause local ischemia and nerve dysfunction.…”
Section: Objectif : La Paralysie Bilatérale Du Sixième Nerf Crânien (mentioning
confidence: 99%
“…4 Magnetic resonance imaging has demonstrated that this results in intracranial hypotension with descent of the brain, even in the supine position, causing traction of the sixth nerve and pain-sensitive structures. 4 The stretching of the nerve is thought to cause local ischemia and nerve dysfunction. 5 This can be seen in association with other signs of intracranial hypotension such as vertigo, nausea, and vomiting.…”
Section: Objectif : La Paralysie Bilatérale Du Sixième Nerf Crânien (mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) reveals diffuse meningeal thickening, gadolinium enhancement, and subdural fluid collections (hygromas and rarely haematomas), at times associated with diminished size of the subarachnoidal cisterns, with the descent of the cerebellar tonsils or with flattening of the optic chiasm [4][5][6][7][8][9]. In such cases, differential diagnosis with systemic diseases like rheumatoid arthritis, mucopolysaccaridosis, sarcoidosis and meningeal carcinomatosis must be performed [10][11][12].…”
Section: B R I E F R E P O R T C Lia (౧)mentioning
confidence: 99%